A novel microstructure of carbide-free bainitic medium carbon steel observed during rolling contact fatigue. (15th March 2016) - Zheng, Chunlei; Lv, Bo; Zhang, Fucheng; Yang, Zhinan; Kang, Jie; She, Li; Wang, Tiansheng
Abstract: A novel microstructure caused by rolling contact fatigue has been observed in a carbide-free bainitic medium carbon steel. The microstructure is associated with localized non-uniform deformation, and is in the form of vortices of plastic deformation centred on non-metallic inclusions in the vicinity of the contact surface. The resulting severe plastic deformation led to the formation of nanocrystalline material, where fatigue cracks initiated and propagated along the upper edge of the nanocrystalline area. Graphical abstract: A novel nanocrystalline area and vortical microstructures (the surrounding area of white dash–dot line) are formed around small non-metallic inclusions in the vicinity of the contact surface of carbide-free bainitic medium carbon steel during the rolling contact fatigue process.